Dukungan Keluarga, Self Efficacy, dan Kecemasan Pasien Gagal Ginjal terhadap Motivasi Menjalankan Hemodialisa (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effect of family support, self-efficacy, and anxiety of kidney failure patients on the motivation to undergo hemodialysis at Undata Hospital, Central Sulawesi Province. This research method uses a cross-sectional design. The results of this study showed that most kidney failure patients undergoing hemodialysis had sufficient family support (95.0%), moderate self-efficacy (95.0%), moderate anxiety (95.0%), and moderate motivation (95.0%). Ordinal regression analysis showed that family support (p 0.001) and anxiety (p 0.000) had a significant effect on patient motivation, while self-efficacy (p 0.368) had no effect. Anxiety (OR 1.065) had a greater effect than family support (OR 1.022), so it became a dominant factor in patient compliance undergoing hemodialysis at Undata Hospital, Central Sulawesi. Conclusion, family support and anxiety significantly influenced the motivation of hemodialysis patients, while self-efficacy had no effect. Anxiety is the dominant factor that influences patient compliance in undergoing therapy. Keywords: Family Support, Anxiety, Motivation, GGK Patients, Self-Efficacy